(untitled) (Global Journal of Medical Research, 2023)
The general objective was to identify the resilience of 3rd and 4th grade students. Semester in time of Covid 19 at the Faculty of Accounting and Administration of the Autonomous University of Chihuahua. It was carried out from March to December 2021. It was a mixed research, of an applied, non-experimental, transactional, hypothetical-deductive, field type with bibliographic support, with a sampling frame obtained from the list of students from the periods January-June and August-December 2021 for the 3rd and 4th semester, provided by the Academic Secretary of the Faculty of Accounting and Administration of the Autonomous University of Chihuahua. Non-probabilistic sampling, for convenience.